The Effects of Higher Bank Capital Requirements on Credit in Peru - Fang, Xiang (IMF Working Papers; Working Paper ;, 2018)
This paper offers novel evidence on the impact of raising bank capital requirements in the context of an emerging market: Peru. Using quarterly bank-level data and exploiting the adoption of bank-specific capital buffers, we find that higher capital requirements have a short-lived, negative impact on bank credit in Peru, although this effect becomes statistically insignificant in about half a year. This finding is robust to estimating different specifications to address concerns about the exogeneity of capital requirements. The fact that the reform was gradual and pre-announced and that banks were highly profitable at the time could explain the short-lived effects on credit.